Tolerance Stack Analysis in Francis Turbine Design - Djodikusumo, Indra; Suherman, Koko; Oken, Paskalis Bowo A. (Journal of Engineering and Technological Sciences, 2010)
TheÂ  toleranceÂ  stackingÂ  problemÂ  arisesÂ  inÂ  theÂ  contextÂ  ofÂ  assemblies fromÂ  interchangeableÂ  partsÂ  becauseÂ  ofÂ  theÂ  inabilityÂ  toÂ  produceÂ  orÂ  toÂ  joinÂ  parts exactlyÂ  accordingÂ  toÂ  nominalÂ  dimensions.Â  EitherÂ  theÂ  relevantÂ  partâsÂ  dimension varies around some nominal valuesÂ  from part to part or the act of assembly that leadsÂ  toÂ  variation.Â  ForÂ  example,Â  asÂ  runnerÂ  ofÂ  FrancisÂ  turbineÂ  isÂ  joinedÂ  with turbine shaft via mechanical lock,Â  there is not only variation in the diameter of runnerÂ  and the concentricity between the runnerÂ  holeÂ  andÂ  turbineÂ  shaft, but also theÂ  variation inÂ  concentricityÂ  betweenÂ  theÂ  outerÂ  partsÂ  ofÂ  runnerÂ  to runner hole. Thus,Â  thereÂ  isÂ  theÂ  possibilityÂ  thatÂ  theÂ  assemblyÂ  ofÂ  suchÂ  interactingÂ  partsÂ  wonât functionÂ  orÂ  wonâtÂ  comeÂ  togetherÂ  asÂ  planned.Â Â  ResearchÂ  inÂ  thisÂ  areaÂ  hasÂ  been conducted and 2 mini hydro Francis turbines (800 kW and 910 kW) have been designed and manufactured for San Sarino and Sawi Dago 2 in Central Sulawesi. ExperiencesÂ  inÂ  analyzingÂ  theÂ  toleranceÂ  stacksÂ  haveÂ  beenÂ  documented.Â  InÂ  this paper it will be demonstrated how the requirements of assembling performance are derived to be theÂ  designedÂ Â Â  tolerancesÂ  of each interacting component, suchÂ  a way that the assembling would be functioning and come together as planned.